Noninvasive and Individual‐Centered Monitoring of Uric Acid for Precaution of Hyperuricemia via Optical Supramolecular Sensing. Issue 18 (28th April 2022) - Zhang, Yaping; Yu, Huijuan; Chai, Shiwei; Chai, Xin; Wang, Luyao; Geng, Wen‐Chao; Li, Juan‐Juan; Yue, Yu‐Xin; Guo, Dong‐Sheng; Wang, Yuefei
Abstract: Characterized by an excessively increased uric acid (UA) level in serum, hyperuricemia induces gout and also poses a great threat to renal and cardiovascular systems. It is urgent and meaningful to perform early warning by noninvasive diagnosis, thus conducing to blockage of disease aggravation. Here, guanidinocalix[5]arene (GC5A) is successfully identified from the self‐built macrocyclic library to specifically monitor UA from urine by the indicator displacement assay. UA is strongly bound to GC5A at micromolar‐level, while simultaneously excluding fluorescein (Fl) from the GC5A·Fl complex in the "switch‐on" mode. This method successfully differentiates patients with hyperuricemia from volunteers except for those with kidney dysfunction and targets a volunteer at high risk of hyperuricemia. In order to meet the trend from hospital‐centered to individual‐centered testing, visual detection of UA is studied through a smartphone equipped with a color‐scanning feature, whose adaptability and feasibility are demonstrated in sensing UA from authentic urine, leading to a promising method in family‐centered healthcare style. A high‐throughput and visual detection method is provided here for alarming hyperuricemic by noninvasive diagnosis. Abstract : A noninvasive and individual‐centered method is accomplished for monitoring uric acid (UA) in urine by executing indicator displacement assay, which successfully differentiates hyperuricemia patients from volunteers and targets a volunteer at high risk of hyperuricemia. To fit the family‐centered healthcare style, optical supramolecular sensing of UA is achieved by reading G value of images acquired with a portable smartphone.